Women “beyond control”? —androcentric discourses in Victorian painting (towards reconstructing meanings) - Gromkowska-Melosik, Agnieszka (Wydawnictwo Naukowe UAM, 2015)
From the perspective of feminist analysis, the painting is considered to be androcentric. It is believed that artworks were created by men, for men and from their point of view. One can even say that, men spoker through the bodies and identities of heroine images in the painting. From this point of view, painting has been accused not only of the lack of women as authors of works of art, but also of the lack of representations of the female experience. Logically, from this perspective, images of women on the canvas are often not simple reflection of reality, but they crystallize dreams, anxieties and feelings of their male artists. There is no doubt that theye are also imbued with ideologies concerning gender. Three images that will be examined in this paper were created in the Victorian era (the dates of their creation are: 1887, 1890, 1896). They all reflect anxieties about womanhood in the late nineteenth century, primarily manifested in the creation of a new image of a woman―the femme fatale. On the other hand the women as objects of the painting are treated as a sexual object for male creator and viewer. Every woman in the paintings could be described as "being out of control.” There is a paradox here: the woman is simultanesly out of control and controlled by men. There is a worth to add that every painting has extremely sugestive impact on the viewer and amazing articstic value.
Keywords: Victorian Painting; femininity; androcentrism; femme fatale; hysteria